2019
DOI: 10.1016/j.ijrobp.2019.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Board Shadowing: A Unique Approach for Integrating Radiation Oncologists Into General Medical Student Education

Abstract: Purpose: Radiation oncology is often overlooked in US medical school curricula, with few opportunities for most students to learn about the specialty or the value of radiation therapy in cancer care. Tumor boards represent a potential avenue not only to increase students' exposure to radiation oncologists but also to provide a fundamental understanding of the multidisciplinary nature of cancer care and effective collaboration in clinical practice. Methods and Materials: In this study, we evaluated a novel radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Study titles and abstracts were screened, and 509 records were excluded. Full-text review was performed on 34 articles, following which, 25 articles were included for qualitative synthesis [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Table 1 summarizes the review findings by data type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study titles and abstracts were screened, and 509 records were excluded. Full-text review was performed on 34 articles, following which, 25 articles were included for qualitative synthesis [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Table 1 summarizes the review findings by data type.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies described initiatives that aimed to teach trainees subjects outside of basic sciences. We identified 6 initiatives that taught or evaluated students about the multidisciplinary nature of oncology, including 2 that focused on teaching psychosocial topics in oncology [ 12 , 19 , 20 , 26 , 27 , 33 ]. Five of the 6 initiatives included some form of interactive learning, including role-playing or shadowing.…”
Section: Resultsmentioning
confidence: 99%
“…It also improved their overall experience and competency. 16 Another approach that has been evaluated is designing a novel radiation oncologist-driven tumor board shadowing experience.…”
Section: Current Preclinical Oncology Initiativesmentioning
confidence: 99%
“…Participation in SRCs is considered extracurricular and students do so on a volunteer basis [2]. Given the depth and complexity of medical education, supplemental experience may augment the learning experience [3][4][5][6]. Studies have shown that early patient exposure and additional clinical experiences can improve student clinical competence [7,8].…”
Section: Introductionmentioning
confidence: 99%